The Role of Women in Preventing Corruption - Saptosih Ismiati (IHSA Institute, 2022)
Women are one of the legal subjects who also influence the law enforcement in society. Currently, many women also play a role in the public sector and organizations, in addition to carrying out their roles as mothers and wives in their families. Women currently have a decisive position in both companies and professions in various fields, so that women have roles as mothers, wives, members of the community or co-workers who have dominant power, one of which is in terms of eradicating corruption in Indonesia. This research is a normative juridical method, namely legal research that refers to written regulations or other legal materials, including statutory approaches, case approaches and conceptual approaches, while the results of the study explain that, corruption is a systemic crime. and endemic, besides that corruption also has a gender dimension, where if there is no comprehensive handling and prevention efforts, it is certain that a country can suffer enormous losses. Women with all the resources that exist in themselves play an important role in the continuation of the life of the generation, women are the closest figures who shape the character of children and give color to their domestic life. Currently, the facts show that women are in the circle of corruption. The powerlessness of women in the public sphere with a corrupt system or accusations of women being one of the causes of corruption in the domestic sphere has increasingly cornered women's position. However, women also have rights and should be involved in every activity related to acts of corruption, considering that Indonesia is one of the countries in the world that has the highest corruption cases compared to several other countries, the participation of women should also be given the opportunity. the same and even more specifically in dealing with every corruption case in Indonesia. The problem of women and corruption has nothing to do with gender identity itself, because the problem of corruption is solely the duty of all citizens and the law has guaranteed it, it cannot be denied that women can also be the spearhead of a country in terms of eradicating corruption.